Students’ Acquisition of Agricultural and Entrepreneurship (Agripreneurship) Knowledge and Skills: Does Instructional Approach and their Sex Matter? - Stephen C. Mukembo; M. Craig Edwards; J. Shane Robinson (Journal of International Agricultural and Extension Education, 2023)
Agricultural and Entrepreneurship education are interdisciplinary due to amalgamating the natural sciences and social sciences. These disciplines have gained the interest of those looking to equip youth with skills for self-reliance. Teachers employ various instructional approaches, including student-centric approaches such as project-based learning (PjBL) and teacher-centric methods, for example, the lecture method, to facilitate learning. Existing research, however, suggests that students’ learning can be influenced by other factors, for example, learning styles, socio-cultural norms, sex stereotypes, and the instructional approach(es) used. We examined the impact of using the lecture method (counterfactual group) versus PjBL (treatment group) approaches on student acquisition of agricultural knowledge in the context of poultry science and their intentions to become agripreneurs. A statistically significant disordinal interaction with a medium effect size was found at p < .05 between groups and student sex for poultry science knowledge. The female students performed better under the PjBL, while the males did so under lecture-based instruction. We also found a statistically significant and positive (p < .05) association between students’ sex and their intent to become agripreneurs for the treatment group. More female students than males in the treatment group indicated they were either likely or highly likely to become agripreneurs in the future. These findings imply that females in the treatment group benefited more from the intervention, PjBL, than their male peers. Additional research should be conducted to measure the long-term impact of using various teaching approaches on students’ learning of agriculture and entrepreneurship content depending on their sex.
Keywords: lecture method; project-based learning (PjBL); supervised agricultural projects (SAPs)